SISTEM MONITORING AKTIVITAS KARYAWAN LAPANGAN DENGAN METODE LOCK GPS BERBASIS CLOUD PADA PTPN II - Heru Irfansyah; Suendri Suendri; Ali Ikhwan (JISTech (Journal of Islamic Science and Technology), 2021)
The GPS Lock method and cloud storage can be applied to the field employee activity monitoring application to be a solution in minimizing the frauds that exist in every employee's job in the field. LOCK GPS can lock the location of employees so that employees can no longer commit dishonesty during absenteeism. To make it easier to monitor employee activities remotely, a menu of employee activity uploads will be provided in the form of photos which will later be completed with the date and time automatically. In harvesting data collection or reports of harvest evidence, a menu is provided to upload photos of the weighing process for harvests and weighing results so that there is no more dishonesty in harvesting data collection. The data for this study were collected through observation, interviews, and relevant literature studies such as journals and books. There are two types of data collected: primary and secondary. By using UML, the steps taken to design the database and describe the workflow of the application to be built. At this stage the author creates an interface that is in accordance with the functions required for the application to be built. RAD (Rapid Application Development) is a system development method used in this research. RAD is a fast-adapted version of the waterfall model that uses a component construction approach.